2019
DOI: 10.1155/2019/3769879
|View full text |Cite
|
Sign up to set email alerts
|

Asparagus Polysaccharide Suppresses the Migration, Invasion, and Angiogenesis of Hepatocellular Carcinoma Cells Partly by Targeting the HIF-1α/VEGF Signalling Pathway In Vitro

Abstract: Hypoxia-inducible factor-1α (HIF-1α) plays a key role by triggering the transcriptional activation of a number of genes involved in migration, invasion, and angiogenesis in hepatocellular carcinoma (HCC). Thus, suppressing tumour growth by targeting the HIF-1α/VEGF signalling pathway represents a promising strategy for the treatment of HCC. In our previous studies, we found that asparagus polysaccharide (ASP) suppressed the proliferation and promoted the apoptosis of HCC cells both in vivo and in vitro. To fur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 49 publications
1
21
1
Order By: Relevance
“…Similar results were reported that Asparagus polysaccharide can induce approximately 80% growth inhibition of HCC cells in comparison to 20% inhibition of LO 2 cells. 14 Hep G2 cell is one of the most widely used cells in the anti-tumor evaluation of Asparagus extracts. 16 , 26 To obtain more information for comparison, Hep G2 cell line was selected for the subsequent experiments.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar results were reported that Asparagus polysaccharide can induce approximately 80% growth inhibition of HCC cells in comparison to 20% inhibition of LO 2 cells. 14 Hep G2 cell is one of the most widely used cells in the anti-tumor evaluation of Asparagus extracts. 16 , 26 To obtain more information for comparison, Hep G2 cell line was selected for the subsequent experiments.…”
Section: Resultsmentioning
confidence: 99%
“…Besides, A. cochinchinensis has multiple pharmacological properties, including anticancer, antioxidation, antifungal, and antiaging activities. [14][15][16][17][18][19] However, the effector mechanism remains partially understood. In this study, A. Cochinchinensis-derived nanovesicles (ACNVs) were isolated, and the antiproliferative activity and apoptosis-inducing mechanism against hepatocellular carcinoma (HCC) were investigated.…”
Section: Introductionmentioning
confidence: 99%
“…The connection of hypoxia and inflammatory signals is well established throughHIF1α gene [ 81 ]. Asparagus polysaccharides potentially inhibited HIF1α signalling which might ameliorate fatal systemic inflammation [ 82 ]. TC also exhibited anti-inflammatory effects in systemic models significantly [ 83 ].…”
Section: Discussionmentioning
confidence: 99%
“…WS showed prophylactic effect in pulmonary hypertension characterised by hypoxia and in ammation 64 . The connection of hypoxia and in ammatory signals is well established throughHIF1α gene 65 .Asparagus polysaccharides potentially inhibited HIF1α signalling which might ameliorate fatal systemic in ammation 66 . TC also exhibited anti-in ammatory effects in systemic models signi cantly 67 .…”
Section: Discussionmentioning
confidence: 99%